The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1128/cvi.00490-09
|View full text |Cite
|
Sign up to set email alerts
|

The Wild-Type Hepatitis C Virus Core Inhibits Initiation of Antigen-Specific T- and B-Cell Immune Responses in BALB/c Mice

Abstract: In this study, the effects of wild-type and deletion mutant hepatitis C virus (HCV) core proteins on the induction of immune responses in BALB/c mice were assessed. p2HA-C145-S23, encoding a core protein with the C-terminal 46 amino acids truncated, significantly produced stronger antibody and cellular responses than p2HA-C191-S23. The induction of immune responses by p2HA-C145-S23 was dose dependent. However, increasing the doses or repeated administration did not enhance immune responses by the wild-type cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 53 publications
(71 reference statements)
0
26
0
1
Order By: Relevance
“…The vectors expressing partial or full length of core and NS3 genes from HCV have been exploited for vaccine purposes routinely due to their suitable immunogenicity and high homology among HCV genotypes (3,7,33,34). Recent publications reported significant controversy regarding to usefulness of full length core protein as vaccine antigen (20,21,24,26,29,35). Some groups of scientists started to use partial fragments of core gene instead of full length genome to overcome shortcomings reported to be associated with the full size core gene such as immunomodulatory and autoimmunity effects (18,24,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vectors expressing partial or full length of core and NS3 genes from HCV have been exploited for vaccine purposes routinely due to their suitable immunogenicity and high homology among HCV genotypes (3,7,33,34). Recent publications reported significant controversy regarding to usefulness of full length core protein as vaccine antigen (20,21,24,26,29,35). Some groups of scientists started to use partial fragments of core gene instead of full length genome to overcome shortcomings reported to be associated with the full size core gene such as immunomodulatory and autoimmunity effects (18,24,26).…”
Section: Discussionmentioning
confidence: 99%
“…However recently published studies demonstrated that both C-and N-terminal domain of HCV core contain autoimmune inducing sequences that maybe harmful for vaccine design (24). Also other studies had shown the immune suppression effect of core protein in animal models and defect of full core gene on immune induction in addition to usefulness of truncated form of core for vaccine purposes (18,(25)(26)(27)(28)(29). In this project, we prepared new expressing vector containing a truncated core gene without Nand C-terminal domain to avoid autoimmunity and/or immune modulatory effects of full length gene.…”
Section: Introductionmentioning
confidence: 99%
“…High expression levels of the HCV C would not induce stronger immune responses but would instead inhibit the priming of immune responses, as shown in the previous studies [29], [44]. The interference of the HCV C with the priming of immune responses to other antigens may reduce the efficacy of combined genetic vaccines.…”
Section: Discussionmentioning
confidence: 81%
“…Earlier studies using a full-length HCV core DNA sequence have revealed a limited immunogenicity of the naked DNA [28], as increasing doses or repeated administration of the full-length HCV core DNA were unable to enhance the specific immune responses [29]. Interestingly, a vector expressing a truncated version of the HCV C improved the induction of specific T- and B-cell responses to the HCV C [28], [29], [30].…”
Section: Introductionmentioning
confidence: 99%
“…Several epitopes specific for T cells were also present in the amino acid region 100–150 of HCV core protein . However, this region has been involved in the deregulation of the immune system and it is toxic for bacteria ; therefore, this region was not included in Eq1 protein.…”
Section: Discussionmentioning
confidence: 99%